Crianças e jovens em situação de vulnerabilidades e a naturalização da(s) violência(s) - Guarnieri, Paola Karuliny (Universidade Federal de São Carlos, 2018)
This research had two main objectives: to analyze whether in the perceptions and life trajectories of the research participants the naturalization of violence is observed; and to identify whether the rights of children and adolescents vulnerable to violence have been ensured. In the qualitative perspective, the participants' narratives were used as a methodological procedure, and as data collection instruments, the presentation of images related to the situation of risk, violence and vulnerability; and the documentary analysis of their medical records written by the social worker of the Service of Coexistence and Strengthening of Family and Community Links - SCFV. We selected nine children and adolescents, aged between seven and fifteen years, enrolled in an institution maintained by the Department of Social Assistance of a city in the interior of the state of São Paulo. To analyze its narratives we elaborate two categories: Vulnerabilities and situations of violence: absence of assured rights; and, Perceptions of violence: fears, overcrowding and naturalization. It was noticed that the selected subjects have their basic rights violated due to the economic and social uncertainty in which they are inserted. Children and adolescents live in precarious conditions that result in the violation of their basic rights, so they can not clearly identify the situations of violence they suffer; on the contrary, they reflect impotence on them, naturalizing them with some hope that something or someone can reverse such circumstances. In this sense, they wait through faith (religion), or they expect that in the future the financial situation of their families will become different. It was concluded that there is an urgent need for investments in this area with public social policies that are responsible for and fulfill the rights of these citizens, as well as innovative research and interventions that can help in this change of society.
Keywords: Adolescentes e violência; Crianças e violência; Populações vulneráveis; Percepção de risco; Violência (Direito); Teenagers and violence; Violence and children; Vulnerable populations; Risk perception; Violence (Law); CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO